Contributing Factors of Cyberbullying Behavior among Youths During Covid-19 - Ira Kusumawaty; Yunike Yunike; Yeni Elviani; Hidayat Arifin (Universitas Airlangga, 2021)
Introduction: The use of information technology during the Covid-19 period is inevitable and can lead to cyberbullying. Mental and life health conditions can be threatened due to being the victim of cyberbullying. This study aims to determine the factors that contribute to the formation of cyberbullying behavior among youths in South Sumatra, Indonesia.Methods: A cross-sectional study was undertaken. The population was youths in South Sumatra, Indonesia with a total sample of 213 respondents who were determined based on purposive sampling. The data collection was done by distributing questionnaires via Google Forms. The questionnaire was developed based on the concept of cyberbullying behavior inclusive of repetition, power imbalance, deliberation and aggression. The data was analyzed using ANOVA and MANOVA.Results: In the study, we found that gender contributes the most to shaping cyberbullying behavior (p=0.000), followed by the parent’s occupation (p=0.018).Conclusion: It is necessary to establish an interconnected system between parents, youth groups and the education sector to avoid cyberbullying behavior. The ability of youths to adapt constructively to the increasing advancement of information technology and to use it wisely is something urgent that needs to be observed so then the cyberbullying cycle can be eradicated.